Serological Investigation and Genetic Characteristics of Pseudorabies Virus in Hunan Province of China From 2016 to 2020 - Lin, Yuan; Tan, Lei; Wang, Changjian; He, Shicheng; Fang, Ling; Wang, Zicheng; Zhong, Yating; Zhang, Kun; Liu, Daoxin; Yang, Qing; Wang, Aibing (Frontiers in Veterinary Science, 2021)
Pseudorabies (PR), caused by variant pseudorabies virus (PRV), is an economicallyimportant viral disease in China. Recently, PRV infection in human has also received attention worldwide. To investigate the PRV infection in Hunan province, China, we collected a total of 18138 serum specimens from 808 PRV-vaccinated pig farms cross this region during 2016-2020, and detected the presence of PRV glycoprotein B (gB) and gE-specific antibodies. The enzyme-linked immunosorbent assay (ELISA) results revealed that 80.47% (14596/18138, 95 CI 79.9-81.0) and 23.55% (4271/18138, 95 CI 22.9-24.2) serum samples were positive for PRV gB and gE-specific antibodies, respectively. Further analysis indicated that the seroprevalence of wild PRV infection was associated with the season and breeding scale (p ˂ 0.01). In addition, five PRV strains were isolated from PRV-positive samples in Vero cells and the virus titers varied from 106.5 to 107.51 TCID50/0.1 mL. The phylogenetic analysis revealed that one isolate was a classical strain of PRV genotype II, and other four isolates belonged to the variants ofgenotype II. Collectively, the data indicate that the prevalence of PRV remains high in pigs in Hunan province, and the variant PRV strains are the major genotypes affecting the development of pig industry.